THE IMPACT OF TECHNOLOGY HELLO ENGLISH APPLICATION IN EFL CLASSROOM - Butarbutar, Ranta; Simatupang, Elia (Lingual Journal of Language and Culture, 2020)
Teacing English as foreign language in junior hogh school forced teacher to used to technology as an interest media to attract student in learning. Chiefly, An application was blasted off by CultureAlley in 2014; hello English has potential to solve student’s problem of understanding simple past tense. To seeing  the using Hello English Aplication giving impact significantly in understanding of simple past tense was the crucial intention of this study. In doing treatment, it used experimental and control class with 46 participants. Crucially, study proven that Data findings and discussion proven 1) there was difference significantly of posttest  between at experiemental class; 95.6% and control class; 60.9% 2) Normality distribution figured out experimental group in posttest is 0.200> ? (0.05) and the significance value of control group in posttest is 0.051>? (0.05). The significance value of both groups are higher than ? (0.05). It means that H0 is accepted and H1 is refused. So, the test distribution of both two groups is normal 3) Homogenity test confirmed ? value (significant value) is higher than ? value. ? > ?, 0,955 > 0,05. Back to the hypothesis, H? is accepted if ? > ?. So it means that the classes are homogeny 4) T-Test  delighted  0.000 < a (0.05) for this reason H0 is rejected and H1 is accepted. Absolutely this study concludes the using hello English Aplication is an interest effective media in learning simple past tense; encouraging self-learning; gadget’s changing better behaviour.   Keywords : i mpact, hello english aplication, simple past tense